Circulating dipeptidyl peptidase 3 and bio-adrenomedullin levels are associated with impaired outcomes in critically ill COVID-19 patients: a prospective international multicentre study. Issue 1 (9th January 2023) - van Lier, Dirk; Deniau, Benjamin; Santos, Karine; Hartmann, Oliver; Dudoignon, Emmanuel; Depret, François; Plaud, Benoit; Laterre, Pierre-Francois; Mebazaa, Alexandre; Pickkers, Peter
Introduction: Dipeptidyl peptidase-3 (DPP3) is a protease involved in the degradation of several cardiovascular mediators. Adrenomedullin (bio-ADM) is a peptide essential for regulation of endothelial barrier function. In different shock-pathologies, both biomarkers are associated with disease severity, organ dysfunction and mortality. Associations with outcome in critically ill COVID-19 patients are unknown. The objectives of the present study were to investigate associations of bio-ADM and "circulating DPP3" (cDPP3) with short-term outcome in critically ill COVID-19 patients (n=80). Methods: A multicentre prospective cohort study was performed. The primary end-point was 28-day mortality. Secondary end-points included different severities of acute kidney injury (AKI). Results: cDPP3 levels were mainly associated with 28-day mortality; Area under the receiver operating characteristics (AUROCs) of 0.69 (0.56–0.82, p=0.023), 0.77 (0.64–0.90, p<0.001) and 0.81 (0.65–0.96, p<0.001) at admission, day 3 and day 7, respectively. In contrast, bio-ADM levels were mainly associated with AKI, with AUROCs of 0.64 (0.51–0.77, p=0.048), 0.75 (0.64–0.86, p<0.001) and 0.83 (0.74–0.93, p<0.001) for day 1, 3 and 7, respectively. Interestingly, patients with high levels of both cDPP3 and bio-ADM at day 7 had an additionally increased risk of 28-day mortality (hazard ratio 11.8; 95% CI 2.5–55.3, p<0.001). Conclusions: cDPP3 and bio-ADM responses were associated with short-term mortality and AKI in critically ill COVID-19 patients, respectively. These findings suggest that treatment with specific antibodies modulating cDPP3 or bio-ADM-related pathways may improve outcome of COVID-19. cDPP3 and bio-ADM responses are associated with short-term outcome in critically ill #COVID19 patients. These findings suggest that treatment with specific antibodies against these biomarkers may improve outcome of COVID-19 patients. https://bit.ly/3SWx3EE